Removal of fluorides from ground waters of coastal Andhra Pradesh in a fixed bed column by using alumina loaded nanoporous Mn-Ce oxide powder adsorbent. (2021) - Rohinikumar, P.; Chandra, K. Sarath; Prasad, C. Durga; Ramesh, K.V.
Abstract: Experiments were conducted to identify the levels of fluorides and chlorides in the ground waters of coastal Andhra Pradesh, India. Samples from ten villages spread across six districts of Andhra Pradesh were obtained and tested for the content of fluorides and chlorides and found that the concentrations of these ions are above permissible levels. Since the ground waters are the major source for drinking water, the people of these areas are more likely to get health problems. In this regard, Mn-Ce-Al adsorbent has been prepared and used in a fixed bed for the removal of these ions. It is found that the adsorbent in the fixed bed is very effective for the removal of fluorides and chlorides from these waters.